The Verb Form Analysis of Arabic Words Using Depth First Search (DFS) Algorithm - Salim, Sulaiman Musthofa; Yazid, Ahmad Subhan (Proceeding International Conference on Science and Engineering, 2019)
Arabic is one of the international languages and the language of the Qur’an widely used in Islam. Learning basic Arabic is important because the language is the foundation of learning Islam. The fault in determining the verb form will relate to wrong meaning. Overcoming the problem, Shorof is a part of the linguistic arabic used to determine the form and utility of a word. Shorof Praktis Krapyak is one of the shorof books that has been widely used by students in Indonesia because of its reliability and simplicity in recognizing the form of Arabic words. The research was conducted to build a system to determine the Arabic verb forms and their utilities by implementing the Depth First Search (DFS) algorithm. DFS is a blind search algorithm in the artificial intelligent discussion that represents a problem into states, generates them systematically and tests them until a goal state is found. Rules made in recognizing the verb form refer to the Shorof Praktis Krapyak which the system is implemented in an Android application. The test results showed that the system can recognize 100 word samples with 100% accuracy. In functionality, all of 30 respondents said that test results stated that the system can run properly. The usability test of the system stated that 55.0% of respondents strongly agreed, 41.6% are agreed and 3.3% choose neutral that this system can help them to recognize and analyze the verb forms in Arabic words.